The Influence Of Brand Image, Online Service Quality , And Of Use On Purchase Decisions On With Trust As A Mediation Variable - Rahayu, Suharni; Limakrisna, Nandan; Horas V. Purba, Jan (Publisher Cv. Inara, 2023)
This research is to determine the effect of Brand Image, Online Service Quality, and Ease of Use on purchasing decisions with Trust as a mediating variable. The population in this study are consumers who have purchased products on the Shopee e-commerce application in South Tangerang. The sample used in this study were 225 respondents. The sampling technique used was purposive sampling. By using a quantitative descriptive approach. Data analysis used statistical analysis with SEM-PLS. The results of this study indicate that Brand Image has a positive and significant effect on Trust. Online Service Quality has a positive and significant effect on Trust. Ease of Use has a significant positive effect on Trust. Brand Image has a negative and insignificant effect on Purchasing Decisions. Online Service Quality has a positive and significant effect on Purchasing Decisions. Ease of Use has a positive and significant effect on Purchasing Decisions. Trust has a positive and significant effect on purchasing decisions.